Pengaruh Literasi Keuangan, Gaya Hidup dan Fintech Digital Payment terhadap Perilaku Pengelolaan Keuangan Generasi Z - Bethanya Sanggarwati; Grace Yulianti; Tanti Sugiharti Singgih (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Generation Z represents an age group most familiar with digital technology and actively engaged in the use of financial technology (fintech) services. Their daily financial activities are closely linked to digital payment platforms, which provide convenience and speed. However, ease of access does not always align with the ability to manage finances wisely, raising concerns about long-term financial health. This study aims to analyze the influence of financial literacy, lifestyle, and the use of fintech digital payment on the financial management behavior of Generation Z in Indonesia. A quantitative research design was employed, with data collected through a structured survey conducted between December 2024 and January 2025. The study involved 128 respondents aged 18–25 years, which exceeded the minimum sample size requirement based on Cochran’s formula, thereby ensuring representativeness. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach, assisted by SmartPLS software. The empirical findings reveal that financial literacy has a positive and significant effect on financial management behavior, suggesting that higher knowledge enables Generation Z to make more informed financial decisions. Similarly, lifestyle exerts a positive and significant influence, indicating that conscious lifestyle choices play an important role in shaping financial habits. In contrast, the use of fintech digital payment does not significantly affect financial management behavior, reflecting that frequent usage of digital payments does not necessarily translate into better financial discipline. These results highlight the urgent need to strengthen financial education programs and promote responsible lifestyle patterns. The study contributes to the understanding of financial behavior among Generation Z and offers insights for educators, policymakers, and fintech providers in developing strategies that foster sustainable financial well-being.